Aspects of Using Biological Regenerative Fuels in Internal Combustion Engines - Lulić, Zoran; Mavrin, Ivan; Mahalec, Ivan (Promet - Traffic&Transportation, 2012)
The work describes some biologically regenerative fuels andcomments on the possibility of their application. Regarding theEuropean conditions, the most acceptable biologically regenerativefuel has proven to be the one based on rape. The characteristicssignificant for the combustion have been compared tothe conventional (fossil) fuels. Also, the impact of biologicallyregenerative fuels on the emission of harmful exhaust gases hasbeen described, and a favourable influence on the emission ofcarbon dioxide (CO2) and other harmful exhaust gases hasbeen determined.